Hubungan Kepribadian Hardiness Dengan Burnout Pada Perawat Gawat Darurat Di RSU GMIM Pancaran Kasih Manado - Faria S. Polapa; Irma M. Yahya; Silvia Dewi Mayasari Riu (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
A tough personality or hardiness in mental health involves efforts to resolve conflict with an individual's cognitive assessment of stressful situations and strategies for dealing with stress. The aim of this research is to determine the relationship between personality hardiness and burnout in emergency nurses at RSU GMIM Pancaran Kasih Manado. The research design used was a descriptive analytical research method which was cross sectional in nature. Until this research used total sampling, namely the sampling technique was the same as the population size. So the total sample in the study was 23 nurses. Data collection was carried out by direct interviews with subjekts and distributing questionnaires. Furthermore, the data that had been collected using computer assistance with IBM SPSS 16.0 was analyzed using the chi-square test with a significance level (α) <0.05. The results of the research using the Chi-Square Test show a p value of 0.162, which is greater than α ≤0.05, meaning that H0 is accepted and Ha is rejected. The conclusion in this study is that there is no relationship between personality hardiness and burnout in emergency nurses at RSU GMIM Pancaran Kasih Manado.